Peptide Modifications: Versatile Tools in Peptide and Natural Product Syntheses - Servatius, Phil; Junk, Lukas; Kazmaier, Uli (Synlett, 2019)
Peptide modifications via C–C bond formation have emerged as valuable tools for the preparation and alteration of non-proteinogenic amino acids and the corresponding peptides. Modification of glycine subunits in peptides allows for the incorporation of unusual side chains, often in a highly stereoselective manner, orchestrated by the chiral peptide backbone. Moreover, modifications of peptides are not limited to the peptidic backbone. Many side-chain modifications, not only by variation of existing functional groups, but also by C–H functionalization, have been developed over the past decade. This account highlights the synthetic contributions made by our group and others to the field of peptide modifications and their application in natural product syntheses.1 Introduction2 Peptide Backbone Modifications via Peptide Enolates2.1 Chelate Enolate Claisen Rearrangements2.2 Allylic Alkylations2.3 Miscellaneous Modifications3 Side-Chain Modifications3.1 C–H Activation3.1.1 Functionalization via Csp3–H Bond Activation3.2.2 Functionalization via Csp2–H Bond Activation3.2 On Peptide Tryptophan Syntheses4 Conclusion
Keywords: C–H activation; natural products; peptide enolates; peptide modifications; total synthesis